Constitutive behavior and microstructural evolution in ultrasonic vibration assisted deformation of ultrathin superalloy sheet. (July 2019) - Meng, B.; Cao, B.N.; Wan, M.; Wang, C.J.; Shan, D.B.
Highlights: The ductility of Inconel 718 ultrathin sheet increases notably with assistance of ultrasonic vibration. The softening effect is unapparent due to the distinct properties of superalloy. The grain misorientations are significantly changed by the ultrasonic vibration. A hybrid constitutive model is developed considering stress superposition and acoustic softening separately. Abstract: Ultrasonic vibration (UV) has been widely applied in metal forming process due to its ability to improve the material properties. However, the mechanical response of difficult-to-deform materials with the assistance of UV is unclear, especially for the ultrathin sheet metals. Meanwhile, the current constitutive models are deficient for the description of UV assisted deformation behavior of the ultrathin material. In this research, UV assisted tensile tests with different amplitudes were performed on the ultrathin superalloy sheet, and the influences on the mechanical characteristic and microstructural evolution were explored. The experimental results indicated that the UV induced softening effect is not evident for high strength material, which is attributed to the tensile deformation characteristic of ultrathin sheet and the distinct mechanical property of superalloy. Nevertheless, the ductility of the superalloy sheet is notably enhanced under the ultrasonic amplitude of 3.18 μm, featured with the increase of elongation from 20.7% to 25.5%. Moreover, the texture is enhanced with increasing ultrasonic amplitude, and the grain misorientations are significantly changed under different UV conditions. To accurately describe the constitutive behavior of superalloy under the assistance of UV, a hybrid constitutive model separately considering stress superposition and acoustic softening effect was developed based on the dislocation evolution theory. The predicted results are in good agreement with the experimental data. These findings provide a more in-depth understanding on the mechanism of UV assisted forming and promote the application of UV assisted manufacturing processes for difficult-to-deform alloys. Graphical abstract: Image, graphical abstract